Evaluation of the In Vivo Bioavailability of Famotidine-loaded 3D-nano-cellulose Networks Produced by Acetobacter xylinum in Selected Culture Media - Thanh, Nguyen Xuan (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4120, 2018)
Abstract: 3D-nano-cellulose networks (3DNC) material has various applications in the biomedical fields and advanced drug delivery systems. 3DNC materials produced from Acetobacter xylinum in standard medium (3DNC-STM), coconut medium (3DNC-COM) and rice medium (3DNC-RIM) were loaded with famotidine by absorption method to obtain famotidine-containing 3DNC to investigate the in vivo bioavailability. The results show that famotidine-loaded M3NCs could produce prolonged release drug delivery, where the extended release time of famotidine-loaded 3DNC-STM and famotidine-loaded 3DNC-COM was higher than famotidine-loaded 3DNC-RIM. The in vivo bioavailability of famotidine-loaded 3DNC-STM was 172%, famotidine-loaded 3DNC-COM was 159%, and famotidine-loaded 3DNC-RIM was 131% compared with the commercial famotidine tablet. Famotidine-loaded 3DNC materials increased the famotidine’s bioavailability in comparison with the commercial famotidine tablet. Keywords: Acetobacter xylinum , in vivo bioavailability, famotidine, prolonged release, 3D-nano-cellulose networks (3DNC). References: [1] X. Zhu, X. Qi, Z. Wu, Z. Zhang, J. Xing, X. Li, Preparation of multiple-unit floating-bioadhesive cooperative minitablets for improving the oral bioavailability of famotidine in rats, Drug Delivery 21 (2014) 459. [2] Lê Thị Phương Thảo, Lê Vĩnh Bảo, Nguyễn Thiện Hải, Nghiên cứu xây dựng công thức và bào chế viên nén famotidine 40 mg, Tạp chí Y học TP. HCM 18 (2014) 72. [3] M. Badshah, H. Ullah, S. A. Khan, J. K. Park, T. Khan, Preparation, characterization and in-vitro evaluation of bacterial cellulose matrices for oral drug delivery, Cellulose 24 (2017) 5041. [4] L. Huang, X. Chen, X. T. Nguyen, H. Tang, L. Zhang, G. Yang, Nano-cellulose 3D-networks as controlled-release drug carriers, Journal of Materials Chemistry B (Materials for biology and medicine) 1 (2013) 2976. [5] B. K. Satishbabu, R. Shurtinag, V. R. Sandeep, Formulation and evaluation of floating drug delivery system of famotidine”, Indian J. Pharm. Sci 72 (2010) 738. [6] M. Anraku, A. Hiraga, D. Iohara, J. D. Pipkin, K. Uekama, Slow-release of famotidine from tables consisting of chitosan/sulfobutyl ether β-cyclodextrin composites, Int. J. Pharm 487 (2015) 142. [7] F. M. Maday, K. A. Khaled, K. Yamasaki, D. Iohara, K. Taguchi, M. Anraku, M. Otagiri, Evaluation of carboxymethyl-beta-cyclodextrin with acid function: improvement of chemical stability, oral bioavailability and bitter taste of famotidine, Int. J. Pharm 397 (2010) 1. [8] R. H. Fahmy, M. A. Kassem, Enhancement of famotidine dissolutionrate through liquisolid tablets formulation: In vitro and In vivo evaluation, Eur. J. Pharm. Biopharm 69 (2008) 993. [9] S. Hestrin, M. Schramm, Synthesis of cellulose by Acetobacter xylinum (2. Preparation of freeze-dried cells capable of polymerizing glucose to cellulose), Biochem J. 58 (1954) 345. [10] Phan Thị Huyền Vy, Bùi Minh Thy, Phùng Thị Kim Huệ, Nguyễn Xuân Thành, Triệu Nguyên Trung, Tối ưu hóa hiệu suất nạp thuốc famotidin của vật liệu cellulose vi khuẩn lên men từ dịch trà xanh theo phương pháp đáp ứng bề mặt và mô hình Box-Behnken, Tạp chí Dược học 501 (2018) 3. [11] Nguyễn Xuân Thành, Đánh giá sự hấp thụ famotidine của cellulose được tạo ra từ Acetobacter xylinum trong một số môi trường nuôi cấy, Tạp chí Khoa học và Công nghệ (Chuyên san Khoa học Nông nghiệp – Lâm nghiệp – Y dược) - Đại học Thái Nguyên 180 (2018) 199. [12] Nguyễn Xuân Thành, Nghiên cứu một số đặc tính của mạng lưới 3D-nano-cellulose nạp curcumin được sản xuất từ vi khuẩn Acetobacter xylinum, Tạp chí Khoa học và Công nghệ (Chuyên san Khoa học Nông nghiệp – Lâm nghiệp – Y dược) - Đại học Thái Nguyên 184 (2018) 83. [13] Nguyễn Xuân Thành, Đánh giá sự giải phóng curcumin của vật liệu cellulose vi khuẩn nạp curcumin định hướng dùng qua đường uống, Tạp chí Khoa học và Công nghệ (Chuyên san Khoa học Nông nghiệp – Lâm nghiệp – Y dược) - Đại học Thái Nguyên 184 (2018) 17. [14] X. T. Nguyen, L. Huang, L. Liu, A. M. E. Abdalla, M. Gauthier, and G. Yang, Chitosan-coated nano-liposomes for the oral delivery of berberine hydrochloride, Journal of Materials Chemistry B (Materials for biology and medicine) 2 (2014) 7149. [15] Phan Thị Huyền Vy, Bùi Minh Thy, Phùng Thị Kim Huệ, Nguyễn Xuân Thành, Triệu Nguyên Trung, Thẩm định phương pháp phân tích định lượng famotidine trong huyết tương thỏ, Tạp chí Y học Thực hành 1 (2018) 46. [16] Trần Thị Thu Hằng, Dược động học lâm sàng, Nhà xuất bản Phương Đông, Hà Nội, 2009. [17] Y. Zhang, M. Huo, J. Zhou, S. Xie, PKSolver: An add-in program for pharmacokinetic and pharmacodynamic data analysis in Microsoft Excel, Comput Methods Programs Biomed 99 (2010) 306. [18] S. K. Jha, R. Karki, V. D. Puttegowda, D. Harinarayana, In Vitro Intestinal Permeability Studies and Pharmacokinetic Evaluation of Famotidine Microemulsion for Oral Delivery, International Scholarly Research Notices (2014) http://dx.doi.org/10.1155/2014/452051. [19] V. Mishra, R. Kaur, Formulation and pharmacokinetic study of famotidine loaded floating microballoons, International Journal of Pharmacy and Pharmaceutical Sciences 4 (2012) 511.